2021
DOI: 10.1039/d0fo02674c
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of immunomodulatory peptides from enzymatic hydrolysates of duck egg ovalbumin

Abstract: Duck egg white (DEW) is considered as an abandoned protein resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Macrophages are essential for the function of immune system because they may destroy infections both directly through phagocytosis and indirectly through the release of cytotoxic chemicals such as NO or cytokines such as TNF-α and IL-6 [ 35 ]. The effects of PEF-treated and untreated peptides on levels of TNF-α and IL-6 in RAW 264.7 cells were analyzed and are presented in Figure 2 D,E.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages are essential for the function of immune system because they may destroy infections both directly through phagocytosis and indirectly through the release of cytotoxic chemicals such as NO or cytokines such as TNF-α and IL-6 [ 35 ]. The effects of PEF-treated and untreated peptides on levels of TNF-α and IL-6 in RAW 264.7 cells were analyzed and are presented in Figure 2 D,E.…”
Section: Resultsmentioning
confidence: 99%
“…TLR 4 is an important part of the TLRs family ( 42 , 43 ). Numerous studies found that TLR 4 recognizes peptides and activates the downstream regulatory signal pathways, such as NF-κB and MAPK, to exert immunomodulatory effects ( 44 , 45 ). Our study showed that the gray value of TLR 4 bands was obviously in control, while the gray value of TLR 4 bands in the model was decreased ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Egg white protein peptide oral liquid is a functional drink made of salted duck egg white through a series of processes such as desalting, enzymatic hydrolysis, and blending. Egg white protein peptide oral liquid is not only easy to digest, but also has a variety of biological activities (He et al, 2021).…”
Section: Desalting Utilization Of Salted Duck Egg Whitementioning
confidence: 99%
“…With a molecular weight of 45 kDa and an isoelectric point between 4.5 and 4.8, ovalbumin is the main protein in duck egg white, accounting for 54% of the total protein of duck egg white (He et al, 2021). Ovalbumin is a phosphoglycoprotein composed of 385 amino acids (Abeyrathne et al, 2014).…”
Section: Nutritional Value Of Salted Duck Egg Whitementioning
confidence: 99%